Crystallographic studies of the extracytoplasmic function σ factor σJ from Mycobacterium tuberculosis. Issue 8 (1st August 2015) - Goutam, Kapil; Gupta, Arvind Kumar; Gopal, Balasubramanian
<x xml:space="preserve">Abstract</x> Mycobacterium tuberculosis has multiple σ factors which enable the bacterium to reprogram its transcriptional machinery under diverse environmental conditions. σJ, an extracytoplasmic function σ factor, is upregulated in late stationary phase cultures and during human macrophage infection. σJ governs the cellular response to hydrogen peroxide‐mediated oxidative stress. σJ differs from other canonical σ factors owing to the presence of a SnoaL_2 domain at the C‐terminus. σJ crystals belonged to the tetragonal space group I422, with unit‐cell parameters a = b = 133.85, c = 75.08 Å. Diffraction data were collected to 2.16 Å resolution on the BM14 beamline at the European Synchrotron Radiation Facility (ESRF).